2013
DOI: 10.3347/kjp.2013.51.6.747
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Ancylostoma duodenale, Ancylostoma ceylanicum, and Necator americanus in Humans in Northeastern and Southern Thailand

Abstract: The 2 principal species of hookworms infecting humans are Necator americanus and Ancylostoma duodenale. Case studies on zoonotic hookworm infections with Ancylostoma ceylanicum and/or Ancylostoma caninum are known mainly from Asian countries. Of these 2 zoonotic species, only A. ceylanicum can develop to adulthood in humans. In the present study, we report a molecular-based survey of human hookworm infections present in southern and northeastern Thailand. Thirty larval hookworm samples were obtained from fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
2
28
1
3
Order By: Relevance
“…However, A. duodenale, A. ceylanicum, and A. caninum were also detected in different parts of the country. 8,13 The predominance of N. americanus in Lower Myanmar is similar to a report from Peninsular Malaysia where N. americanus was more common than A. ceylanicum, but A. duodenale infection was not discovered. 10 In contrast, a report from Lao PDR people found that infections due to A. duodenale and the animal hookworms, A. caninum and A. ceylanicum, were slightly more prevalent than those due to N. americanus.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…However, A. duodenale, A. ceylanicum, and A. caninum were also detected in different parts of the country. 8,13 The predominance of N. americanus in Lower Myanmar is similar to a report from Peninsular Malaysia where N. americanus was more common than A. ceylanicum, but A. duodenale infection was not discovered. 10 In contrast, a report from Lao PDR people found that infections due to A. duodenale and the animal hookworms, A. caninum and A. ceylanicum, were slightly more prevalent than those due to N. americanus.…”
supporting
confidence: 83%
“…Each genus and species of hookworm infecting humans has its own distinct biology, life cycle, pathophysiology, and epidemiology, knowledge of which therefore impacts on designing control measures. 6 A molecular approach to identification is therefore imperative and copro-molecular methods for species identification of hookworms have been reported in neighboring countries (Thailand, 8,13 Lao People's Democratic Republic [PDR], 14 and Cambodia 6,15 ). Molecular methods were used to identify as A. ceylanicum a case of hookworm infection in a French individual who had visited Myanmar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, infections of hookworms and O. viverrini are the major public health problems [15, 16, 25, 30, 33]. Infections of zoonotic hookworms, A. ceylanicum and A. caninum , have been reported in many areas [25, 33].…”
mentioning
confidence: 99%
“…Infections of zoonotic hookworms, A. ceylanicum and A. caninum , have been reported in many areas [25, 33]. Molecular analysis showed A. ceylanicum is prevalent in humans and dogs in the Central and the Northeastern areas of Thailand [25, 33]. Prevalence and species of zoonotic hookworms in dogs and cats in the lower Northern area of Thailand are still unknown.…”
mentioning
confidence: 99%